STUDY OF PREVALENCE OF MULTI-DRUG RESISTANT ACINETOBACTER SPECIES IN VENTILATOR-ASSOCIATED PNEUMONIAE CASES IN A TERTIARY CARE HOSPITAL, VISAKHAPATNAM - RANI, MATTAM SUNEETHA; VANI, THAMMINA MEHER SRI SAI SUDHA; SAILAJA, B. S. G. (International Journal of Current Pharmaceutical Research, 2024)
Objective: Acinetobacter sps are important oppurtunistic pathogens with their significance in colonising and persistent biofilm production capabilities. The aim of the present study was to assess the prevalence of multidrug-resistant Acinetobacter sps in ventilator-associated pneumoniae cases in a tertiary care hospital Visakhapatnam. Methods: A prospective study was conducted on 328 endotracheal aspirate samples received in Clinical Laboratory, Department of Microbiology for a period of 1 y, from June 2023 to June 2024, in mechanical ventilated cases, admitted in intensive care units, in a tertiary care hospital, Visakhapatnam. Results: Out of 328 samples received, 42 (12.8%) were Acinetobacter isolates with resistance to Aminoglycosides (66.7%), Cephalosporins (57.1%), Quinolones (52.4%), Carbapenems (42.9%). Biofilm production was identified in 31 isolates (73.8%) by Congo Red Agar method in this study. Conclusion: The potential ability of Acinetobacter sps to form biofilms and antibiotic selective pressure leading to emergence of resistant clones is directly proportional to the injudicious use of antibiotics. There is a strict need of antibiotic stewardship measures in intensive care units to restrict development of pan-resistant strains.